Analisis Film Kartini Dalam Perspektif Kesetaraan Gender - Fansier Hamdja; Fathul Qorib; Sulih Indra Dewi (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2020)
The purpose of this study was to determine the efforts of gender equality contained in the Kartini film through the semiotic study of Roland Barthes. Roland Barthes's analysis is used to find out the meaning of denotation, connotation, and myth in an image contained in artistic visualization, act, and dialogue in the film "Kartini". The results of this study that the connotation meaning of the Kartini film in the perspective of gender equality is an effort to fight for gender equality by Kartini as a woman who likes to write and teach literacy to others while denotative meaningthe effort to fight for gender equality in Kartini's film is that Kartini struggles through the path of literacy because literacy is a good way to fight for gender equality, with literacy she breaks Javanese culture which considers women unequal to men andhave abilities below men.Keywords: Semiotics, Kartini, Gender equality.Â Keywordsâ€”: Semiotics; Kartini; Gender Equality.